Biological and pharmacological functions of the FGF19- and FGF21-coreceptor beta klotho - Aaldijk, Alexandra S.; Verzijl, Cristy R. C.; Jonker, Johan W.; Struik, Dicky (Frontiers in Endocrinology, 2023)
Beta klotho (KLB) is a fundamental component in fibroblast growth factor receptor (FGFR) signaling as it serves as an obligatory coreceptor for the endocrine hormones fibroblast growth factor 19 (FGF19) and fibroblast growth factor 21 (FGF21). Through the development of FGF19- and FGF21 mimetics, KLB has emerged as a promising drug target for treating various metabolic diseases, such as type 2 diabetes (T2D), non-alcoholic fatty liver disease (NAFLD), and cardiovascular disease. While rodent studies have significantly increased our understanding of KLB function, current clinical trials that test the safety and efficacy of KLB-targeting drugs raise many new scientific questions about human KLB biology. Although most KLB-targeting drugs can modulate disease activity in humans, individual patient responses differ substantially. In addition, species-specific differences in KLB tissue distribution may explain why the glucose-lowering effects that were observed in preclinical studies are not fully replicated in clinical trials. Besides, the long-term efficacy of KLB-targeting drugs might be limited by various pathophysiological conditions known to reduce the expression of KLB. Moreover, FGF19/FGF21 administration in humans is also associated with gastrointestinal side effects, which are currently unexplained. A better understanding of human KLB biology could help to improve the efficacy and safety of existing or novel KLB/FGFR-targeting drugs. In this review, we provide a comprehensive overview of the current understanding of KLB biology, including genetic variants and their phenotypic associations, transcriptional regulation, protein structure, tissue distribution, subcellular localization, and function. In addition, we will highlight recent developments regarding the safety and efficacy of KLB-targeting drugs in clinical trials. These insights may direct the development and testing of existing and future KLB-targeting drugs.